PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN DAN BIAYA KEPATUHAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBAD - Putri Gantine Lestari; Rika Januar Heriyadi (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2019)
The purpose of this research is to analyze the influence of the modernization of thetax administration system and cost of compliance with individual taxpayer compliance at SukabumiTax Office. The method used in this study is the Explanatory method with a survey approach. Thepopulation in this study are individual taxpayers at Sukabumi Primary Tax Office.To taking thesample used by simple random method. The number of samples is determined as many as 100people. Primary data collection method used in this research by using a questionnaire. Dataanalysis techniques used in this research is multiple linear regression analysis technique. Based onresearch, the modernization of tax administration and compliance costs simultaneously affect thecompliance of Individual Taxpayers.